Implementasi hukum lingkungan melalui penyuluhan pemilahan sampah di Desa Kesiman Kertalangu - Ramadiansyah, Sahri Aflah; Indradana, Gde Nararya (Politeknik Kesehatan Kemenkes Aceh, 2025)
Education on waste sorting is an important strategy in implementing environmental law at the community level. This research aims to analyze the effectiveness of waste sorting education carried out by PEPS officers in Kesiman Kertalangu Village. The method used is a qualitative approach with interviews and observation as data collection techniques. The research results show that this outreach not only increases public awareness about the importance of waste segregation, but also strengthens compliance with existing environmental regulations. In addition, active community participation in this program contributes to reducing the volume of waste and improving environmental quality. The conclusion of this research recommends the need to increase the frequency and quality of education so that more people are involved and understand legal aspects related to waste management.Keywords: Environmental Law, Counseling, Waste Sorting